Analisis Kinerja Simpang Tak Bersinyal di Kota Malang (Studi Kasus Jalan S. Supriadi - Jalan Satsui Tubun Kecamatan Sukun) - Agung, Stefanus Leo; Sa'dillah, M.; Primasworo, Rifky Aldila (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
The intersection of Jalan S. Supriadi - Jalan Satsui Tubun is a connecting route between Malang city and other cities. So to minimize the conflict in the intersection of Jalan S. Supriadi - Jalan Satsui Tubun, serious handling is needed. So that researchers are interested in studying further through research with a quantitative approach method of descriptive type. The implementation of this research aims to analyze the performance of Jalan S. Supriadi - Jalan Satsui Tubun in the existing and the next 10 years and recommend appropriate handling techniques at the intersection. Then to support data analysis, researchers implemented two types of data sources, namely secondary data sources in the form of the number of vehicle growth and population, while the primary data was in the form of intersection geometric conditions and traffic volume. Data collection was carried out for 7 days. The results of the traffic performance analysis showed that the value of vehicle volume in 2023 was 5249 cur/ hour, the degree of saturation (DJ) value obtained was 1.0> 0.85, meaning that the speed level was slow and the flow was experiencing obstacles, so it fell into category F for the level of service and the delay was 28.3 sec /cur service level B (less). From the analysis results for the next 10 years, the degree of saturation (DJ) on Jalan S. Supriadi - Jalan Satsui Tubun still meets the requirements based on PKJI 2014. In 2023, the traffic volume levels on the east, south, and north approaches are 666 pcu/h, 979 pcu/h, and 1042 pcu/h respectively, while the degree of saturation on the east, south, and north approaches are 0.71; 0.49; and 0.71 respectively.